Nilai-Nilai Ulil Albab sebagai Fondasi Generasi Emas: Kajian QS. Ali ‘Imran 190–194 dalam Tafsir Ibn Katsir - Mellani Putri Rahayu Buwono; Dzulkifli Hadi Imawan (Peradaban Journal of Religion and Society, 2026)
This article examines the concept of Ulil Albab in the Qur’an and its relevance as a foundation for Islamic education in responding to the challenges of the contemporary digital era. Amid rapid technological disruption, the formation of human resources who possess not only intellectual competence but also spiritual depth and moral integrity has become increasingly urgent. Employing a descriptive qualitative approach based on library research, this study analyzes QS. Ali ‘Imran (3): 190–194 through the interpretive framework of Ibn Katsir’s Tafsir. The analysis focuses on identifying the core characteristics of Ulil Albab and their educational implications. The findings indicate that education grounded in the values of Ulil Albab is structured upon the integration of dhikr (remembrance of God), fikr (critical reflection), and amal ṣāliḥ (righteous action); the centrality of tawḥīd; a balanced development of spiritual, intellectual, and social dimensions; a commitment to knowledge and wisdom; and adherence to truth and noble character. The study further demonstrates that the implementation of these values in education requires character-based learning, an integrative curriculum, active pedagogical strategies, the role of teachers as murabbī, and collaboration across educational environments. This research contributes to Islamic educational discourse by offering a Qur’anic value-based framework for cultivating a holistic and ethically grounded generation capable of navigating the complexities of the digital age. Artikel ini mengkaji konsep Ulil Albab dalam Al-Qur’an serta relevansinya sebagai fondasi pendidikan Islam dalam merespons tantangan era digital kontemporer. Di tengah pesatnya disrupsi teknologi, pembentukan sumber daya manusia yang tidak hanya unggul secara intelektual, tetapi juga memiliki kedalaman spiritual dan integritas moral menjadi kebutuhan yang semakin mendesak. Penelitian ini menggunakan pendekatan kualitatif deskriptif berbasis studi kepustakaan dengan menganalisis QS. Ali ‘Imran (3): 190–194 melalui kerangka penafsiran Ibn Katsir. Analisis difokuskan pada identifikasi karakteristik utama Ulil Albab dan implikasinya bagi pendidikan Islam. Hasil penelitian menunjukkan bahwa pendidikan berbasis nilai-nilai Ulil Albab dibangun atas integrasi dzikr (mengingat Allah), fikr (refleksi kritis), dan amal saleh; penguatan nilai tauhid; keseimbangan antara dimensi spiritual, intelektual, dan sosial; kecintaan terhadap ilmu dan hikmah; serta komitmen terhadap kebenaran dan akhlak mulia. Penelitian ini juga menegaskan bahwa implementasi nilai-nilai tersebut dalam pendidikan menuntut penguatan pendidikan karakter, pengembangan kurikulum integratif, penerapan metode pembelajaran aktif, peran pendidik sebagai murabbi, serta sinergi antarlingkungan pendidikan. Dengan demikian, penelitian ini memberikan kontribusi konseptual bagi pengembangan pendidikan Islam berbasis nilai Qur’ani guna membentuk generasi yang unggul secara holistik dan adaptif terhadap perubahan zaman.